Anthropometric, physiological characteristics and rugby-specific game skills discriminating Zimbabwean under-16 male adolescent rugby players by level of competition - Chiwaridzo, M.; Ferguson, G. D.; Smits-Engelsman, B. C. M. (BMJ Open Sport & Exercise Medicine, 2019)
Objectives Despite growing popularity of adolescent rugby in Zimbabwean schools, little is known about qualities or skills of schoolboy rugby players and how they differ by competitive level. Therefore, the aim of the current study was to identify anthropometric, physiological characteristics and rugby-specific game skills capable of discriminating under-16 (U16) RU players across three proficiency levels.